Frontiers in the Roman World Proceedings of the Ninth Workshop of the International Network Impact of Empire (Durham, 16-19 April 2009) - Hekster, Olivier; Kaizer, Ted (Impact of Empire, 2011)
This volume presents the proceedings of the ninth workshop of the international network 'Impact of Empire', which concentrates on the history of the Roman Empire. It focuses on different ways in which Rome created, changed and influenced (perceptions of) frontiers. Readership: All those interested in Roman history (also at the local level in communities in the Roman Empire), frontier-studies, politics and administration in the classical world, and the connections between centre and periphery within the Roman Empire.